Privacy preserving monitoring protocol for Cyber–Physical System. (September 2022) - Roy, Pradeep Kumar; Singh, Sunil Kumar
Abstract: Cyber–Physical Systems integrate computational and physical systems that can interact with humans in various ways. Due to less research on location privacy, building a monitoring protocol for the CPS system is challenging. Location privacy is becoming a major issue in the CPS, where the actual source and its messages are kept avoided by an attacker. The attacker follows the incoming message's route to reach the source's location. To hide the location of the source from attackers and increase their safety period, this research proposes a Multi-Ring protocol. A complete theoretical and mathematical analysis is discussed to check the model's complexity and performance. The message delivery delay, throughput, energy consumption, and safety time ratio metrics are used for performance comparison. The simulation results confirmed that the proposed protocol increases the source safety period and network lifetime compared to the existing protocols.